Analysis of Efficiency and Marketing Structure of Cocoa Commodities in Lasusua District, North Kolaka Regency - Iqbal, Haeryl; Sappareng, Sukriming; Yumna, Yumna (Universitas Syiah Kuala, 2025)
This study aims to analyze the structure, efficiency, and marketing margins of cocoa in North Kolaka Regency, focusing on two main distribution channels. Channel I follows the Farmer Collector/Wholesaler Factory pattern, with a marketing margin of Rp. 10,081/kg, while Channel II follows the Farmer Company pattern, with a margin of Rp. 7,329/kg. Efficiency calculations indicate that Channel I has an efficiency level of 0.25% and Channel II 0.21%, with lower percentage values indicating higher cost efficiency. Market concentration analysis using the concentration ratio of the four largest companies (CR4) yielded a value of 92%, indicating a very strong oligopoly market structure approaching monopoly. This condition indicates that pricing, supply volume, and product quality standards are heavily influenced by a handful of dominant players. Although product distribution is efficient, the high level of market concentration poses a risk of dependence on dominant players and barriers to entry for new players. Therefore, strengthening competition regulations, empowering farmer institutions, limiting distribution chains, and implementing product innovation strategies are necessary to improve the bargaining position of farmers and the cocoa supply chain.